A dual nozzle 3D printing system for super soft composite hydrogels. (April 2021) - Dine, Andi; Bentley, Edward; PoulmarcK, Loic A; Dini, Daniele; Forte, Antonio E.; Tan, Zhengchu
Graphical abstract: Highlights: An advanced 3D printing system for composite material tissue scaffold fabrication. Utilises a liquid-solid printing ink phase change for structural printing stability. The synergistic cryogel printing ink enables super soft 3D structures to be created. The dual nozzle extrusion system allows for the construction of complex architectures. Abstract: Due to their inability to sustain their own weight, 3D printing materials as soft as human tissues is challenging. Hereby we describe the development of an extrusion additive manufacturing (AM) machine able to 3D print super soft hydrogels with micro-scale precision. By designing and integrating new subsystems into a conventional extrusion-based 3D printer, we obtained hardware that encompasses a range of new capabilities. In particular, we integrated a heated dual nozzle extrusion system and a cooling platform in the new system. In addition, we altered the electronics and software of the 3D printer to ensure fully automatized procedures are delivered by the 3D printing device, and super-soft tissue mimicking parts are produced. With regards to the electronics, we added new devices to control the temperature of the extrusion system. As for the software, the firmware of the conventional 3D printer was changed and modified to allow for the flow rate control of the ink, thus eliminating overflows in sections of the printing path where the direction/speed changes sharply.